Employee Retention As a Mediation Variable of Career Development and Reward Management System that Impact Prevention Turn Over Employee - Supardi; Kamsariaty; Wenny Desty Febrian; Josua Panatap Soehaditama; Bekti Setiadi (Indonesian Journal of Advanced Research, 2023)
The purpose of this study is to see how much the independent variable contributes to the dependent variable and to see the indirect effect of the intervening variable. This study wants to test the effect of independent and intervening variables on the dependent variable, to determine the significance between variables. The results of this study after looking at the literature review that has been analysed that there is significance between variables. This research uses a literature review study that does not use respondents as the basis for data processing. To prevent turnover in an organization the company must have an employee retention career development program for employees and implement a reward management system.